D8.1. Report on overall sites infrastructure preparation - Larat, Emmanuel
The objective of work package WP8 is to ensure a timely preparation and availability of the infrastructures of pilot sites in order to allow the installation of the LITES system. Preparation of the infrastructures is own financing and consequently doesn’t request EC funding. An other objective is to ensure the coordination for a correct and timely implementation and putting into service of the pilot projects. Each pilot site should name a person responsible for local follow-up. Each responsible will report to the overall follow-up. This Deliverable is dedicated for Task 8.1. “Overall follow-up of preparation and installation” and Task 8.2 “Local coordination on infrastructures preparation”.